Food Insecurity: Does It Push Married Women to Participate in Labor Force? - Ririn Kuncaraning Sari; Dwy Bagus Cahyono (Institut Teknologi Sepuluh Nopember, 2019)
Women's labor force participation in Indonesia tends to be lower than men. In married women, decisions to participate in labor force are more complicated related to their duties at home. Economic difficulties is one of the reason for their participation. This research aims to look the relationship of household food insecurity that illustrates the economic difficulties and material hardship of the family to the woman labor force participation. Using 2017 Susenas survey, this paper assesed food insecurity from Food Insecurity Experience Scale (FIES). The results show that labor force participation in married women is 50,05 percent where most of the married women work in informal sector (60,31 percent). However, probit regression shows that tendencies of married women to participate into labor market higher with the severity of the food insecurity. Married women who experience severe food insecurity 6,3 point percent more likely to participate in the labor force than the one who has food security. But overall, education, husband’s working status and type of residence are the strongest determinant of married women labor force participation.